REGRESI LINEAR BERGANDA DALAM UJI PENGARUH SIKAP DAN PERILAKU TERHADAP KEINGINAN MENABUNG SANTRI PADA BANK SYARIAH - Navirta Ayu; Ahmad Zamroni; AHMAD SYAFII RAHMAN; Toto Hermawan (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2021)
Economy is the main thing and must be experienced by every human being in this world, so that the economy is always developing so rapidly, so is the Islamic economy which is currently developing rapidly to compensate for conventional economics. The Islamic economy has a function as a filter for the economic activities of every Muslim in the world, because in the concept of its implementation it has principles based on the strength of the Muslim Al-Qur'an and Sunnah that avoid usury, gharar and maysir. This study uses a quantitative method, which uses a questionnaire as a measurement tool, while the object of research is the Islamic boarding school students in Yogyakarta, and the variables studied are the attitude and behavior of students toward saving desires in Islamic banks. The results showed that the students 'attitudes and behavior had a positive effect on students' desire to save at Islamic banks.